Intensi Whistleblowing Mahasiswa Akuntansi STIE Studi Ekonomi Modern : Teori Planned Behavior (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of attitudes, subjective norms, perceived behavioral control, and retaliation on whistleblowing intentions among accounting students at STIE STEKOM. Data were collected through questionnaires to 80 respondents, then analyzed using IBM SPSS Statistics. The validity test showed that all question items had a Corrected Item Total Correlation value greater than r table (0.182), thus declared valid. The reliability test produced a Cronbach's Alpha value of 0.877 for all variables, indicating a reliable instrument. The classical assumption test included multicollinearity (tolerance > 0.10, VIF < 10), heteroscedasticity (Sig. > 0.05), and normality (Sig. K-S = 0.245 > 0.05) which met the requirements. The results of the regression analysis showed that attitudes, perceived behavioral control, and retaliation had a significant positive effect on whistleblowing intentions, while subjective norms had a negative effect. The F test proved that the independent variables simultaneously had a significant effect on whistleblowing intentions. The coefficient of determination (Adjusted R²) of 56.6% indicates that the model is able to explain variation in whistleblowing intentions, while the remaining 43.4% is influenced by other factors. This finding confirms the importance of individual and environmental factors in driving whistleblowing behavior